An Approach of LSB- Symmetric Cryptography to Secure Classified Text Content - Sharma, R; Dwivedi, A; Namdeo, V (International Journal of Computer Sciences and Engineering, 2018)
The proposed idea provides information that obscures the idea with the combination of cryptography and steganography. Proposed ideas are important to support verification, confidentiality and fairness. To achieve these effects, the main idea is to use a symmetric cryptography system for privacy and validation security, mainly an incomplete reliability key supported by the steganography method. The proposed idea is primarily dependent on the security with the coding of the emission data is covered in the first phase and the data in the next phase encrypted discharge, so that it ensures a double security for a discharge date. Exhibited steganography idea, image or content as the information first (as a picture) coded and packaged by correlation with minimal image collective size after compressed data were shaken by symmetric cryptographic process using a private key of 128 bits of coded data, this private key splits via a private channel between the sender and the payee, and finally inserts encrypted data into the bitplanes of the title image using the smallest noteworthy piece (LSB) of the standard stereographic procedure. To achieve a high security strategy, the proposed steganography strategy has used random numbering (RAND) which selects an irregular LSB from the envelope. The results shown demonstrate the implementation and feasibility of the proposed proposal for inclusion of the peek flag on sedimentation rate (PSNR), compound and entropy.